2010
DOI: 10.4049/jimmunol.0803474
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of the Ectonucleotidase CD39 on T Cells from the Inflamed Site Identifies Two Distinct Populations, One Regulatory and One Memory T Cell Population

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
116
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 49 publications
20
116
2
2
Order By: Relevance
“…This supports previous studies where CD39, in combination with other Treg-cell surface markers, identified a population of human FOXP3 + suppressive Treg cells [11,14,43,44].…”
Section: Discussionsupporting
confidence: 79%
“…This supports previous studies where CD39, in combination with other Treg-cell surface markers, identified a population of human FOXP3 + suppressive Treg cells [11,14,43,44].…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with this, a recent study in juvenile RA patients reported a correlation between low CD73 expression and disease severity (7). In contrast, CD73 levels on jointinfiltrating immune cells have been shown to be decreased in some patients with juvenile RA (8).…”
supporting
confidence: 67%
“…It would be most interesting to assess whether deregulated CD73 expression and/or CD73 gene polymorphisms are associated with increased susceptibility to RA. In juvenile RA, for instance, where MTX displays considerable heterogeneity response rates, reduction of CD73 activity on mononuclear cells has been reported (8). Although correlation between CD73 polymorphism and autoimmunity has not been reported, a recent study by S. Robson and colleagues (16) revealed that polymorphisms in CD39 (ectonucleoside triphosphate diphosphohydrolase 1), a cell membranebound enzyme acting upstream of CD73 by converting ATP or ADP to AMP, is associated with increased susceptibility to inflammatory bowel disease in humans.…”
Section: Discussionmentioning
confidence: 99%
“…According to functional experiments performed by us (see Fig. S2 in the supplemental material) and others (38), the capability of Tregs to suppress proliferation seems to be confined exclusively to the CD4 ϩ , CD25 high , CD39 ϩ cell compartment. At the moment, it remains speculative whether CD39 acts as a switch for the suppressive function of Tregs.…”
Section: Discussionmentioning
confidence: 99%